The Effects of Antitrust Laws on Horizontal Mergers: International Evidence - Chung, Chune Young; Hasan, Iftekhar; Hwang, JiHoon; Kim, Incheol (Journal of financial and quantitative analysis, 2024)
This study examines how antitrust law adoptions affect horizontal merger and acquisition outcomes. Using the staggered introduction of competition laws in 20 countries, we find antitrust regulation decreases acquirers’ 5-day cumulative abnormal returns surrounding horizontal merger announcements. A decrease in deal value, target book assets, and industry peers’ announcement returns are consistent with the market power hypothesis. Exploiting antitrust law adoptions addresses a downward bias to an estimated effect of antitrust enforcement. The potential bias from heterogeneous treatment effects does not nullify our results. Overall, antitrust policies seem to deter post-merger monopolistic gains, potentially improving customer welfare.